Hematopoietic-Derived Galectin-3 Causes Cellular and Systemic Insulin Resistance - Li, Pingping; Liu, Shuainan; Lu, Min; Bandyopadhyay, Gautum; Oh, Dayoung; Imamura, Takeshi; Johnson, Andrew M F; Sears, Dorothy; Shen, Zhufang; Cui, Bing; Kong, Lijuan; Hou, Shaocong; et al. (Cell, 2016)
In obesity, macrophages and other immune cells accumulate in insulin target tissues, promoting a chronic inflammatory state and insulin resistance. Galectin-3 (Gal3), a lectin mainly secreted by macrophages, is elevated in both obese subjects and mice. Administration of Gal3 to mice causes insulin resistance and glucose intolerance, whereas inhibition of Gal3, through either genetic or pharmacologic loss of function, improved insulin sensitivity in obese mice. In vitro treatment with Gal3 directly enhanced macrophage chemotaxis, reduced insulin-stimulated glucose uptake in myocytes and 3T3-L1 adipocytes and impaired insulin-mediated suppression of glucose output in primary mouse hepatocytes. Importantly, we found that Gal3 can bind directly to the insulin receptor (IR) and inhibit downstream IR signaling. These observations elucidate a novel role for Gal3 in hepatocyte, adipocyte, and myocyte insulin resistance, suggesting that Gal3 can link inflammation to decreased insulin sensitivity. Inhibition of Gal3 could be a new approach to treat insulin resistance.